2001
DOI: 10.1103/physrevlett.86.4911
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Spectroscopy ofBi2Sr2CuO6+δ

Abstract: Using scanning tunneling spectroscopy, we investigated the temperature dependence of the quasiparticle density of states of overdoped Bi(2)Sr(2)CuO(6+delta) between 275 mK and 82 K. Below T(c) = 10 K, the spectra show a gap with well-defined coherence peaks at +/-Delta(p) approximately 12 meV, which disappear at T(c). Above T(c), the spectra display a clear pseudogap of the same magnitude, gradually filling up and vanishing at T(*) approximately 68 K. The comparison with Bi(2)Sr(2)CaCu(2)O(8+delta) demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
130
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 25 publications
38
130
2
Order By: Relevance
“…There are two different proposals to explain the PG; one is associated with the formation of local incoherent pairs above T c (precursor pairing) [1] and the other is not directly related to the superconductivity and rather competes with superconductivity [2,3,4]. The former is based on the experimental results from angleresolved photoemission spectroscopy (ARPES) [5,6,7] and tunneling spectroscopy [8,9], which demonstrate a smooth evolution of the superconducting (SC) gap into the PG across T c , and the overall d-wave symmetry of PG [10,11]. The latter scenario is based on ARPES [12,13,14,15], tunneling spectroscopy [16], and Raman scattering [17] studies, which reported two different types of energy gaps; a SC gap which opens below T c in the nodal region and an antinodal PG whose magnitude shows a T -independence across T c .…”
mentioning
confidence: 99%
“…There are two different proposals to explain the PG; one is associated with the formation of local incoherent pairs above T c (precursor pairing) [1] and the other is not directly related to the superconductivity and rather competes with superconductivity [2,3,4]. The former is based on the experimental results from angleresolved photoemission spectroscopy (ARPES) [5,6,7] and tunneling spectroscopy [8,9], which demonstrate a smooth evolution of the superconducting (SC) gap into the PG across T c , and the overall d-wave symmetry of PG [10,11]. The latter scenario is based on ARPES [12,13,14,15], tunneling spectroscopy [16], and Raman scattering [17] studies, which reported two different types of energy gaps; a SC gap which opens below T c in the nodal region and an antinodal PG whose magnitude shows a T -independence across T c .…”
mentioning
confidence: 99%
“…The σ(V ) curves have an inverted parabolic shape, which might indicate the presence of van-Hove singularity close to the Fermi level in slightly OD samples. The behaviour of the SG in UD samples at T → T c is one of the most important and yet controversial issues [12,17]. For UD samples the peak is much weaker than for OD samples even at low T , cf.…”
Section: Temperature and Doping Dependenciesmentioning
confidence: 99%
“…The term pseudogap has been coined to describe this kind of physics. The presence of pseudogap has been established through the measurements of the nuclear magnetic resonance (NMR) [5], the scanning tunneling spectroscopy [6][7][8][9], the analysis of the electronic Raman scattering [10][11][12], through time-resolved optical spectroscopy [13][14][15][16][17][18], and through the ARPES [19][20][21][22][23][24][25]. The observed strong Nernst effect in cuprates has been also attributed to it [26][27][28].…”
Section: Introductionmentioning
confidence: 99%